(untitled) (Current Horticulture, 2024)
There are quite a large number of indigenous and underutilized fruit crops, which are used by the local inhabitants. In fact, these fruits are the only source of protective food to meet the need of vitamins and minerals of people living in villages. Owing to curative properties, these fruits are used in Ayurvedic and Unani medicines since time immemorial. Apart from their nutritive and medicinal values, a few underutilized fruits have excellent flavour and very attractive colour.Their cultivation is very restricted and they grow mainly as wild. Being tolerant to biotic and abiotic stresses, these fruit crops are suitable for growing in the drought prone areas.Since India has a rich heritage of indigenous fruit types, some of them have already been recommended for commercial planting. It is apparent that there are more fruit crops that await future exploitation. Semi-arid fruits are the oldest fruit tree crops with wide distribution, reflecting their adaptation to a wide range of edapho-climatic conditions of our country. The understanding of various agro-techniques, propagation methods, canopy management, and biotic and abiotic stresses management are equally important for improving their productivity and quality. These crops are known as underutilized but they are locally abundant, and restricted to their geographical location owing to dearth of scientific knowledge. These crops like bael, jamun, tamarind, chironji, khirni custard apple, etc. are immensely constructive and climate smart by surviving in harsh agroclimatic conditions, and can be established on degraded lands, which are presently being underutilized. Therefore, to review the research work done and exploring lacunae in these potential crops critically has become the need of the hour. Hence, research review paper deals all issues and challenges pertaining to these fruit crops.